2017
DOI: 10.1177/0170840616685590
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Conditions and Paradoxical Frames

Abstract: Organizational contexts establish conditions that seem paradoxical, but it is unclear when and why individuals notice and respond to paradoxes. This paper examines how culture and conditions interact to shape whether individuals adopt paradoxical frames. We used cooperation and competition among American and Chinese people as an empirical setting. Using lay categories as a theoretical framework, we predicted that specific types of conditions, colleagues' outperforming and out-helping each other, can be interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 79 publications
0
121
0
2
Order By: Relevance
“…; Keller et al . ; Miron‐Spektor et al . ; Smith and Tushman ), and similarly with intuition and analysis (see below).…”
Section: Overview Of Paradox Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…; Keller et al . ; Miron‐Spektor et al . ; Smith and Tushman ), and similarly with intuition and analysis (see below).…”
Section: Overview Of Paradox Theorymentioning
confidence: 99%
“…Prior literature has found that East Asians are more likely to have a higher paradox mindset (Keller et al . ), but are less likely to reap the creative and performance benefits of a paradox mindset (Leung et al . ).…”
Section: Managers’ Approaches To Tensions Between Intuition and Analysismentioning
confidence: 99%
See 3 more Smart Citations